(untitled) (Journal of Applied Learning and Teaching, 2023)
Numerous university graduates are actively looking for professional learning development (PLD) possibilities to help them adapt to a wide range of professional roles and responsibilities. For these reasons, this paper aims to create a research-based framework for graduate professional development that considers the shifting nature of the labour market. The purpose of this paper was to summarize and build upon prior research on graduates’ PLD through an integrative theoretical translation approach. To develop a strategy for PLD, the author consulted with relevant parties and analyzed data gleaned from surveys, interviews, and scholarly articles. The four essential pillars of the PLD framework are acculturation, career skills, astuteness, and competence. There are 16 categories under each of the four primary domains, each representing a different collection of abilities and skills that a graduate can acquire once they leave university. Graduates, their supervisors, and higher education institutions can use the framework to better prepare students for post-graduation life and job.